Analisis Penerapan Sistem Informasi Akuntansi Persediaan Studi Kasus Pada CV. Bina Usaha Sejahtera Malang - Alodia Salsabila Putri Wijaya (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The rapid development of the industry has made the level of competition even tighter. Companies need to pay attention to several things in the face of competition, one thing that really needs to be considered in the order fulfillment process is the need for an effective and efficient inventory system. The purpose of this research is to find out the implementation of inventory accounting information systems in CV. Prosperous Business Development. The method used by researchers for this research is descriptive qualitative method with primary data and secondary data types. The research results obtained are the Accounting Information System contained in the CV. Bina Usaha Sejahtera is still not optimal, one of the contributing factors is the double duty of the warehouse department.